Stefan problem for the laplace equation with regard for the curvature of the free boundary - Bazalii, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider a nonstationary problem with free boundary for an elliptic equation in the case where the value of the required function on an unknown boundary is proportional to the curvature of this boundary. We prove the existence of a solution in the small with respect to time in the spaces of smooth functions.